Competitive Intelligence (CI) as a business strategy in the sustainability of delivery services in the era of the industrial revolution 4.0 - Yusup Iskandar; Nurdiana Mulyatini; Mukhtar Abdul Kader (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The company growing among its competitors is something that needs to be maintained where the company gets the right steps to know the business development of its competitors. This study uses a qualitative research method based on the philosophy of postpositivism. Shipping service companies to survive in the midst of competition must have a strategy, namely Competitive Intelligence so that they are able to take on the strategies of their competitors with changes in the demographic, economic, sociocultural, global, technological and political environment. Information on products, industry, vendors, customers, competitors and markets obtained is used as material to be applied in the company. Competitive Intelligence delivery services obtained information namely delivery speed, range, fleet, service, price, search marketing, web design and management of information systems. POS is a delivery service that has the widest range and the fastest J&T. Winning the competition. Shipping services must implement what is expected of the Industrial revolution 4.0.